Structural Change and Lead-Lag Relationship between the Nikkei Spot Index and Furure's Price: A Genetic Programming Approach - Lien, Donald (Institutional Knowledge at Singapore Management University, 2003)
In this paper we adopt a nonparametric genetic programmingÂ (GP) approach to identify the structural changes in the Nikkei spot index and futures price. Due to the dominance of the â€˜normalâ€™ period in sample data, the lead-lag relationship identified in the spot-futures system based on conventional methods such as the test for Granger causality pertains to the normal period and may not be applicable in an â€˜extremeâ€™ period. Using GP we identify the lead-lag relationship based on the chronological ordering of the structural changes in the spot and futures markets. Our results show that in recent periods, major market changes originated from the spot market and spread over to the futures market.